2019
DOI: 10.1039/c9sc00415g
|View full text |Cite
|
Sign up to set email alerts
|

Targeting extracellular glycans: tuning multimeric boronic acids for pathogen-selective killing of Mycobacterium tuberculosis

Abstract: Innovative chemotherapeutic agents that are active against Mycobacterium tuberculosis (Mtb) are urgently required to control the tuberculosis (TB) epidemic.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“… 18 , 19 In addition, recent studies have suggested that boronic acid groups are very useful for bacterial targeting because of their ability to form a pair of covalent bonds with glycans on the surface of bacteria. 20 – 22 Therefore, the 3-{ N -(4-boronobenzyl)- N , N -dimethylammonium}phenoxy-substituted zinc( ii ) phthalocyanine PcN4-BA ( Fig. 1a ) was herein designed to be a new PS for antimicrobial PDT.…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 In addition, recent studies have suggested that boronic acid groups are very useful for bacterial targeting because of their ability to form a pair of covalent bonds with glycans on the surface of bacteria. 20 – 22 Therefore, the 3-{ N -(4-boronobenzyl)- N , N -dimethylammonium}phenoxy-substituted zinc( ii ) phthalocyanine PcN4-BA ( Fig. 1a ) was herein designed to be a new PS for antimicrobial PDT.…”
Section: Introductionmentioning
confidence: 99%
“…This presents a disadvantage for enriching many low-abundance glycopeptides that may be outcompeted during the enrichment process. Recently, several reports have shown that boronic acid–glycan interactions can be enhanced through screening of boronic acid compounds or through increasing avidity via dendrimeric boronic acid–functionalized materials ( 345 , 346 , 349 , 350 , 351 ).…”
Section: Chemical Coupling Strategiesmentioning
confidence: 99%
“…Guy et al. 32 designed multimeric boronic acids to selectively target structurally unique Mtb cell envelope glycans, in order to overcome the Mtb cell envelope barrier ( Fig. 20 ).…”
Section: Boron-containing Antibacterial Agentsmentioning
confidence: 99%
“…The boronic acid pharmacophore is an established glycan-binding functional group that forms reversible complexes with diol groups commonly found in sugar molecules and glycoproteins 28 , 29 , 30 , 31 . Exploiting this behavior, multimeric boronic acids have been designed to target pathogens’ extracellular glycans, both to overcome inherent cell envelope barriers and to prevent the development of drug resistance 32 . Boronic acid-containing prodrugs of hydroxylated drug molecules have also been developed to reduce first-pass metabolism and thus to increase bioavailability 33 , 34 , 35 .…”
Section: Introductionmentioning
confidence: 99%